The Threat of Exploitation in the Adult Sex Market: A Pilot Study of Online Sex Worker Advertisements. (18th March 2017) - Skidmore, Michael; Garner, Sarah; Desroches, Callyane; Saggu, Nikhita
Abstract: Trafficking and exploitation are central elements of the serious and organized crime threat for local police forces to deal with, but remain largely hidden because victims seldom approach the police or other authorities for help. This pilot study explores the potential for harnessing information posted online to flag up sex workers who are most at risk. A single website used by sex workers to advertise and make contact with customers was examined, and all phone numbers and relevant profile information were extracted for those advertising sexual services in the south-west of England. Of the sex workers, 9% were found to advertise with phone numbers that were the same or in close proximity to another advertising on the website, and these online profiles were found to share multiple additional similarities. A number of profiles also included information that suggested a vulnerability to exploitation. This is intended as a preliminary study to explore the potential and applicability of using these data, and ways to develop the methodology and the implications for practice are discussed.